تحليل الميزة التنافسية في المصارف السورية باستخدام المؤشرات الذاتية (دراسة مقارنة بين المصرف التجاري السوري ومصرف سورية والمهجر) - ناصر الدين زينا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تتميز البيئة الاقتصادية الحديثة بمتغيراتها التي تتسم بحالة من عدم الاستقرار نتيجة ظروف المنافسة المتزايدة والتطور التكنولوجي الكبير في مختلف المجالات، مما يفرض على مختلف القطاعات الاقتصادية ومن ضمنها المصارف السعي المستمر لمواكبة التطورات والبحث عن مزايا تنافسية تجعلها قادرة على الاستمرار والبقاء في السوق. يهدف البحث إلى دراسة مدى تحقيق المصارف السورية للميزة التنافسية بالاعتماد على المؤشرات الذاتية من خلال مقارنة تطور المؤشرات الذاتية لكل من المصرف التجاري السوري ومصرف سورية والمهجر. وتمت صياغة فرضية رئيسة يتفرع عنها ثلاثة فرضيات فرعية، تم اختبارها بواسطة الحزمة الإحصائية للعلوم الاجتماعية Statistical Package for Social Sciences،SPSS V(23), لتتوصل الباحثة إلى عدة نتائج أهمّها: يحقق كل من المصرف التجاري السوري ومصرف سورية والمهجر ميزة تنافسية، حيث يتفوق المصرف التجاري السوري في مؤشرات كفاية رأس المال والسيولة نوعية الموظفين، بينما يتفوق مصرف سورية والمهجر في مؤشر نظم المعلومات والتكنولوجيا. The modern economic environment is characterized by its unstable variables due to the increasing competition conditions and the great technological development in various fields. This requires various sectors of the economy, including banks, to continuously strive to keep abreast of developments and to find competitive advantages that will enable them to continue and stay in the market. The aim of the research is to study the extent to which Syrian banks have achieved competitive advantage based on the subjective indicators by comparing them of the Commercial Bank of Syria and the Bank of Syria and overseas. A basic hypothesis was drawn up, with three sub-hypotheses, which were tested by the Statistical Package for Social Sciences, SPSS V (23). The researcher came up with several results, the most important of which are: The Commercial Bank of Syria and the Bank of Syria and overseas achieve a competitive advantage, Commercial Bank of Syria outperforms in the indices of capital adequacy and liquidity and quality of employees, while the Bank of Syria and overseas outperforms in the index of information systems and technology.